Knowledge, attitudes and delivery mode preferences among pregnant women in a tertiary hospital, Nepal - Gupta, Bidhya (Janaki Medical College Journal of Medical Science, 2026)
Background & Objectives: Caesarean section (CS) is life‑saving when medically indicated, yet increasing CS use without clear indications is a global concern. Women’s knowledge and attitudes influence their preferences and can shape demand for CS. The study aimed to assess knowledge, attitude, and preference toward mode of delivery among pregnant women attending the antenatal clinic of National Medical College, Birgunj. Materials and Methods: An analytical cross‑sectional design was applied to the dataset of total 140 respondents. The knowledge was rated on a 0-44 scale and was divided into poor (<50%) and fair ((50–<75%) and good (≥75%). The participants were assessed on attitudes toward vaginal delivery and CS with two 9-item Likert subscales and were defined as positive (≥60) or negative (<60). The chi-square tests and multivariate logistic regression were used to examine the association. Results: Mean age was 25.7±3.8 years. Most participants had poor knowledge (58.6%), a negative attitude toward vaginal delivery (60.7%), and a positive attitude toward CS (67.9%). Preference for CS was 50.7%. Knowledge level was associated with preference (p=0.027); compared with fair knowledge, poor knowledge was associated with higher odds of preferring CS (AOR=3.42, 95% CI 1.34–8.69). Conclusions: Preference for CS was common and co‑existed with limited knowledge and less favorable attitudes toward vaginal birth. Antenatal counseling that supports informed choice and addresses fear, misinformation, and local drivers of CS may help align preferences with evidence‑based care.